Communication Disorder of The Autistic Character in The “Fly Away” Movie - Nadira Dinda Prastiwi; Rohmani Nur Indah (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2020)
This study aims to identify the type of communication disorder in comprehending the speech of an autistic character in the “Fly Away” movie. In addition, it aims to describe the occurrence of communication disorders. In this study, the researchers used the theory on the type of communication disorder (Paul, 2008). As the findings, there are forty-three data of the five types of communication disorders namely, repetition of words, minimal response, limitation of communication function, use of unusual words, and low frequency. The result stated that word repetition is a type of disorder that often occurs in autistic characters in “Fly Away”. The occurrence of communication disturbance is also sown by several incidents such as, jumping, excessive laughs, rebellion, repeating posture, eyes up, just see the interlocutor and bite the fingers. These things are an expression that happened to the autistic character when experiencing communication disorders. This finding can be used as a guideline for those interacting with autistic individuals applying both verbal and nonverbal communication.